Effect of Addition of Methionine and Lysine into Diets Based on Cafeteria Standards on the Growth Performance of Native Chickens at Starter Phase - Lisnahan , Charles V.; Wihandoyo; Zuprizal; Harimurti, Sri (International Journal of Poultry Science, 2017)
Objective: The aim of this study was to determine the effect of the addition of methionine and lysine to feed based on cafeteria standards of native chickens on their growth performance (0-6 weeks). Materials and Methods: A total of 288 days-old native chickens (DOC) were used in this study. The DOC were divided into 4 treatments groups with 4 replications. The treatment diets were T0 and T1 (according to cafeteria and NRC standards) and T2 and T3, which were based on cafeteria standards with the addition of 0.14% methionine and 0.40% lysine for T2 and 0.27% methionine and 0.79% lysine for T3. The data collected were feed intake, body weight, feed conversion ratio and carcass as a percentage of body weight. Results: The results showed that the feed intake of T0, T1, T2 and T3 were 516.97, 556.91, 621.79 and 654.30 g/bird/6 weeks, respectively. The body weights for each group were 219.09, 232.67, 267.16 and 284.61 g/bird/6 weeks, respectively. The feed conversion data were 2.79, 2.80, 2.66 and 2.61, respectively and the carcass percentages were 53.20, 52.75, 54.63 and 56.85%, respectively. Conclusion: Feed formulated to cafeteria standards with the addition of 0.27% methionine and 0.79% lysine (group T3) resulted in the best growth performance.